Bahts Naqd 'An al-Jumlah 'Ind al-Nuhat wa Atsaruh Fi al-Ta'lim - Aisyah, Devy (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This study aims to critic the concepts of classical and modern Arabic linguists about sentences which they term differently including: number, kalam, tarkib (sentence, phrase). Their differences are inseparable from polemics, especially in providing boundaries and terms used, both in the classical and modern eras. For example the polemic on the use of terminology and the number and meaning of both, whether synonymous or not, which then affects the elements that build it. This study uses a literature study (library research) with content analysis and hermeneutic approaches. This research found that basically the differences in Arabic experts both in the classical and modern eras were not substantive, but rather as editorial debates, technical terminology, and partial.The old grammarian tended to be complicated in providing a definition of sentence compared to contemporary Islamic scholar, Â it was easier to explain about this sentence.